2008
DOI: 10.1177/0748730408320486
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference of the Clock GeneperiodDisrupts Circadian Rhythms in the CricketGryllus bimaculatus

Abstract: Periodic expression of so-called clock genes is an essential part of the circadian clock. In Drosophila melanogaster the cyclic expression of per and tim through an autoregulatory feedback loop is believed to play a central role in circadian rhythm generation. However, it is still elusive whether this hypothesis is applicable to other insect species. Here it is shown that per gene plays a key role in the rhythm generation in the cricket Gryllus bimaculatus. Measurement of per mRNA levels in the optic lobe reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 51 publications
10
91
0
Order By: Relevance
“…per is an important circadian clock gene in D. melanogaster (Konopka and Benzer, 1971;Baylies et al, 1987), and circadian oscillation of per mRNA or distribution of per-expressing neurons has been shown in different insect orders (Frisch et al, 1996;Sauman and Reppert, 1996;Goto and Denlinger, 2002;Wise et al, 2002;Hodková et al, 2003;Závodská et al, 2005;Iwai et al, 2006;Codd et al, 2007;Moriyama et al, 2008). However, few studies have demonstrated that per or per-expressing neurons are functionally important for circadian behavioural rhythms or photoperiodism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…per is an important circadian clock gene in D. melanogaster (Konopka and Benzer, 1971;Baylies et al, 1987), and circadian oscillation of per mRNA or distribution of per-expressing neurons has been shown in different insect orders (Frisch et al, 1996;Sauman and Reppert, 1996;Goto and Denlinger, 2002;Wise et al, 2002;Hodková et al, 2003;Závodská et al, 2005;Iwai et al, 2006;Codd et al, 2007;Moriyama et al, 2008). However, few studies have demonstrated that per or per-expressing neurons are functionally important for circadian behavioural rhythms or photoperiodism.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have demonstrated that per or per-expressing neurons are functionally important for circadian behavioural rhythms or photoperiodism. In G. bimaculatus, it has been reported that per knockdown by RNAi suppresses circadian rhythms in locomotor activities and electrical activities of optic lobe neurons (Moriyama et al, 2008). In M. sexta, surgical ablation of per expressing neurons from larval brains caused loss of photoperiodic control of pupal diapause (Wise et al, 2002;Shiga et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a circadian rhythm modifying the circatidal rhythm by inhibiting activity during subjective day free-runs under constant darkness and can be entrained by light -dark cycles [9]. In insects, the molecular basis of the circadian clock has been extensively studied [10], and the predominant role of the gene period (per) is confirmed in some species, including a cricket, Gryllus bimaculatus [11]. Thus, the mangrove cricket is a suitable subject for examining the molecular basis of the circatidal rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there seem to be considerable differences in the molecular oscillatory mechanism among insects. In crickets, the role of clock genes has been examined in a more direct way using RNA interference (RNAi) [61][62][63]. Like other insects, the expression of cricket's per gene cycles in a daily fashion in both LD and DD, and peaks at early night.…”
Section: Results In Other Insects Do Not Fully Support the Drosophilamentioning
confidence: 99%
“…Like other insects, the expression of cricket's per gene cycles in a daily fashion in both LD and DD, and peaks at early night. Double stranded RNA (dsRNA) of per knocks down per mRNA levels, and disrupts both its cycling and the locomotor activity rhythm [61]. Functional analysis with RNAi of other clock genes will clarify the molecular oscillatory mechanism in the cricket.…”
Section: Results In Other Insects Do Not Fully Support the Drosophilamentioning
confidence: 99%